Neurological effects of inorganic arsenic exposure: altered cysteine/glutamate transport, NMDA expression and spatial memory impairment - Ramos-Chávez, Lucio A.; Rendón-López, Christian R. R.; Zepeda, Angélica; Silva-Adaya, Daniela; Del Razo, Luz M.; Gonsebatt, María E. (Frontiers in Cellular Neuroscience, 2015)
Inorganic arsenic (iAs) is an important natural pollutant. Millions of individuals worldwide drink water with high levels of iAs. Chronic exposure to iAs has been associated with lower IQ and learning disabilities as well as memory impairment. iAs is methylated in tissues such as the brain generating mono and dimethylated species. iAs methylation requires cellular glutathione (GSH), which is the main antioxidant in the central nervous system. In humans, As species cross the placenta and are found in cord blood. A CD1 mouse model was used to investigate effects of gestational iAs exposure which can lead to oxidative damage, disrupted cysteine/glutamate transport and its putative impact in learning and memory. On postnatal days (PNDs) 1, 15 and 90, the expression of membrane transporters related to GSH synthesis and glutamate transport and toxicity, such as xCT, EAAC1, GLAST and GLT1, as well as LAT1, were analyzed. Also, the expression of the glutamate receptor N-methyl-D-aspartate (NMDAR) subunits NR2A and B as well as the presence of As species in cortex and hippocampus were investigated. On PND 90, an object location task was performed to associate exposure with memory impairment. Gestational exposure to iAs affected the expression of cysteine/glutamate transporters in cortex and hippocampus and induced a negative modulation of NMDAR NR2B subunit in the hippocampus. Behavioral tasks showed significant spatial memory impairment in males while the effect was marginal in females.